Menggali pandangan ushul fiqih terhadap cryptocurrency - SAIDAH, NOVICA ERLIYANA NUR (Maliki Interdisciplinary Journal, 2026)
Rapid technological innovation has introduced cryptocurrency as a decentralized digital alternative for payments. Given its growing influence, a comprehensive study is required to determine its validity under Islamic law as either a medium of exchange or a commodity. This research employs a qualitative method with a literature review approach, analyzing journals, ushul fiqh texts, and relevant books to evaluate its Sharia compliance. The findings indicate that while the state recognizes cryptocurrency solely as a commodity, it is deemed invalid under Islamic law as both a currency and a commodity. This conclusion is based on the fact that cryptocurrency inherently contains elements that void trade contracts in Sharia: riba (usury), gharar (uncertainty), and maysir (gambling/speculation). From the perspective of ushul fiqh, its prohibition is rooted in the Quran (Surah An-Nisa: 29 and Surah Al-Maidah: 50) and Hadiths regarding speculative transactions. Furthermore, through qiyas (analogy), cryptocurrency is compared to hablu al-hablah (the sale of an unborn camel fetus), which is forbidden due to jahalah (ambiguity of the object) and the resulting gharar. Ultimately, cryptocurrency is considered haram due to these pervasive elements of uncertainty and speculation